Rainwater harvesting system using a non-parametric stochastic rainfall generator. (June 2013) - Fulton, Lawrence V; Bastian, Nathaniel D; Mendez, Francis A; Musal, R Muzaffer
With water becoming an even scarcer resource, rainwater harvesting (RWH) systems are becoming increasingly more commonplace as mechanisms to capture and store rainwater for both agricultural and domestic use. Three important engineering considerations associated with the construction of RWH systems are the capture surface area, the tank volume required for specific demand levels, and the number of expected occupants. The purpose of this work is to evaluate the engineering design of a RWH system in a semi-arid Texas region using a non-parametric stochastic rainfall generator based on 64 years of data and to provide engineering charts and equations for future use. We model the RWH system using simulation techniques in order to estimate requirements for building a system capable of providing a family with 100% of its water requirements with demand never exceeding available supply (100% demand satisfaction).